IMPROVING STUDENTS’ READING COMPREHENSION BY USING REAP (READ, ENCODE, ANNOTATE, PONDER) STRATEGY - Vera Maria Santi (Linguists : Journal Of Linguistics and Language Teaching, 2015)
This research was a classroom action research. The objective of this research was to explain the extent to which the using REAP Strategy can improve students’ reading comprehension and factors improved the students’ reading comprehension at the second year students of VIII.2 class of SMPN 14 Kota Bengkulu. The subjects of this research were 37 students, consisted twenty two (22) males and fifteen (15) females. The instruments of this research were reading comprehension tests, students’ and teacher’s observation checklists and field notes, and interview. The research was conducted in two cycles which included plan, action, observe, and reflect. The evaluation test was given at the end of each cycle. The result of this research shows that using REAP strategy successfully improved students’ reading comprehension. There were 83,7% students reached the very good category or got the score ≥75. The improvement was influenced by the used of interesting materials chosen, the REAP strategy, and the teacher attitudes toward the students